Colonic contained perforation of unknown etiology treated conservatively in a 34 year old female patient: a case report - Hordejuk, Michalina; Marczak, Aleksandra; Gołacki, Jakub; Sapuła, Klaudia; Iwaszko-Sochal, Klaudyna (Journal of Education, Health and Sport, 2022)
A colon perforation is defined as a disruption in the continuity of the gastrointestinal wall. A contained perforation is a situation where the perforation is self-limited, usually by adhesion to other structures in the abdominal cavity. Many conditions can cause perforation, including cancer, diverticular disease, or iatrogenic perforation such as during an endoscopy procedure. Less commonly, the cause may be inflammatory bowel disease or the presence of a foreign body in gastrointestinal tract. Furthermore, there are also publications describing situations of spontaneous rupture of the intestinal wall, i.e. spontaneous perforations. This group includes spontaneous perforation caused by fecal stones and idiopathic perforation. In this article we present a case report of a 34 year old woman with perforation of the large intestine without any apparent cause. We discuss the differential diagnosis of patients with conservatively treated perforation with unknown colonoscopy result.